Information Communication Technology (ICT) in Educational Institutions and Strategic Initiatives - Basri, Wael Sha.; Siam, Mohammed R A (International Journal of Engineering and Technology, 2018)
Information Communication Technology (ICT) has impacted educational institutions not only with the communication equipment and software and hardware devices, a satellite system for video conferencing as a distance learning support system but also it has changed the inter personal relationships between teachers and students and alsoÂ the role of the educational institutions. If through the application of ICT, the education sector has witnessed growth in terms of student enrollments in programs like distance learning, e-learning, and open learning, ICT has also proved a useful strategic tool to drive the core business of the educational institution as an organization. The ICT strategy of an educational institution consists of three strategic programmers namely the knowledge management programme, the resource management programme and the infrastructure management programme. At the policy levels, in some higher educational institutions, strategic planning and policy development are a priority and a series of ICT strategic initiatives are taken in matters related to business, operations, technology and human resources. This paper explores all these strategies in the light of ICT and its various applications in higher educational institutions.